Factors influencing global transportation electrification: Comparative analysis of electric and internal combustion engine vehicles - Tan K.M.; Yong J.Y.; Ramachandaramurthy V.K.; Mansor M.; Teh J.; Guerrero J.M. (Elsevier Ltd, 2024)
Leaders worldwide have committed to tackling climate change and adopted climate-related measures to reduce greenhouse gas emissions. Transportation electrification is one of these measures taken to achieve carbon neutrality and requires the replacement of fossil-fueled internal combustion engine (ICE) vehicles with electric vehicles (EVs). EV adoption has accelerated in several countries over the past decade. Nonetheless, the EV adoption pace remained uneven throughout the globe as many factors affect the social acceptance of EVs. Additionally, dissimilar economic conditions, driving behaviors, population densities, societal norms, educational backgrounds, and geographical conditions among the countries further complicate the consumers' purchasing intentions. This article analyzed the competitiveness of EVs compared to ICE vehicles based on the nations market demands. The research focuses on China, Europe, the United States, Japan, South Korea, India, Thailand, Indonesia, and Malaysia. The comparative analysis was conducted in terms of vehicle performance, charging infrastructure, government policy, and social factors. Strategies to promote EV adoption include introducing price-competitive EV models, importing affordable EVs, strengthening EV purchase incentives, extending driving ranges, diversifying battery manufacturers, subsidizing electricity for EVs, developing public charging infrastructure, offering EV rental and sharing programs, promoting EV-enabled technologies, and increasing the use of renewable energy in electricity generation and EV manufacturing. The suggested measures aim to address market demand and improve the competitiveness and social acceptance of EVs. By sharing experiences and implementing effective strategies, countries can accelerate the transition to electric transportation and mitigate the environmental impacts of the automotive sector. 2023 Elsevier Ltd